Prototipe Alat Pengusir Burung pada Gedung Berbasis Internet of Things menggunakan Sensor RCWL - Khumaidi, Ali (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2020)
Sound disturbance and bird droppings in buildings are a problem for building managers. Bird droppings are quite difficult to remove and cause damage to the walls and aesthetics, especially the trend in the use of building roofs as a rooftop for productive activities. This study proposes the use of RCWL motion sensors for motion detection and the resulting output is the sound of eagles from speakers and ultrasonic speakers. The tool was developed based on internet of things using an arduino nano ATMega 328 microcontroller, connection and data transmission using SIM800L and GSM modules and power supply using a solar panel power bank. The test results show that the RCWL motion sensor is quite optimal in the detection of more than or equal to 3 birds. Sound output and the resulting waves are able to prevent birds from alighting and nesting.